PERLINDUNGAN HUKUM TERHADAP TERASI SEBAGAI PRODUK INDIKASI GEOGRAFIS DI KOTA LANGSA PROVINSI ACEH - Trohna, Dyona Rizky; Saidin, Saidin; Sembiring, Rosnidar; Leviza, Jelly (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
Geographical indication is a sign that indicates the origin of goods and/or products that, due to geographical factors including natural factors, human factors, or a combination of both, impart specific reputation, quality, and characteristics to the goods and/or products produced. Terasi is one of the leading products in Langsa City that supports the local economy, but it has not yet been registered as a geographical indication, despite its potential to be recognized as such due to its distinct characteristics compared to other terasi products, thus warranting legal protection.This research uses an empirical juridical approach, with data sourced from primary, secondary, and tertiary legal materials. Data collection techniques include library research and field research, involving interviews and document studies. The data analysis used is qualitative analysis.The results of the research show that terasi meets the criteria for being classified as a geographical indication product under the Trademark and Geographical Indication Law, to receive legal protection once it is registered with the Directorate General of Intellectual Property. Given its unique characteristics, terasi is distinct from other terasi products. Efforts by local authorities to encourage the development of legal protection for geographical indications for terasi in Langsa City include coordination with local officials to plan socialization activities aimed at educating the community, especially terasi producers, on the importance of registering terasi as a geographical indication. Obstacles to providing legal protection include suboptimal roles by local government, a lack of understanding and awareness among the community about the importance of geographical indication protection, and the absence of community organizations that protect geographical indications.